Optimization of Biodegradable Films from Avocado Seed Starch Using Response Surface Methodology - Alif Nur Laili Rachmah; Sabrianah Badaruddin; Tamaratritania Citta Trisnantari; Geraldi Rahanra; Ratri Sekaringgalih (Journal of Green Chemical and Environmental Engineering, 2026)
This study aimed to develop and optimize biodegradable films based on avocado seed starch (Persea americana) using glycerol as a plasticizer and chitosan and carrageenan as fillers. The film formulation was optimized using Response Surface Methodology (RSM) with a Box–Behnken Design to evaluate the effects of formulation variables on biodegradability and mechanical properties. The biodegradability values ranged from 31.93 % to 51.94 %, indicating that all films were biodegradable. Increasing glycerol and carrageenan concentrations significantly increased biodegradability, while higher chitosan concentration improved tensile strength but reduced biodegradability. The optimal formulation was obtained at 2.96 % glycerol, 1.56 % chitosan, and 2.85 % carrageenan, with a predicted biodegradability of 53.11 %. The results indicate a trade-off between mechanical strength and biodegradability, where higher plasticizer content enhances degradation but reduces tensile strength. This study demonstrates that RSM optimization is effective in producing biodegradable films with balanced mechanical and environmental performance, highlighting the potential of avocado seed starch as a sustainable packaging material.